DNA Binding and Cleavage by the Fowlpox Virus Resolvase - Culyba, Matthew J. (American Society for Biochemistry and Molecular Biology, 2009)
The first steps of poxvirus DNA synthesis yield concatemeric arrays of covalently linked genomes. The virus-encoded Holliday junction resolvase is required to process concatemers into unit-length genomes for packaging. Previous studies of the vaccinia virus resolvase have been problematic due to poor protein solubility. We found that fowlpox virus resolvase was much more tractable. Fowlpox resolvase formed complexes with a variety of branched DNA substrates, but not linear DNA, and had the highest affinity for a Holliday junction substrate, illustrating a previously unappreciated affinity for Holliday junctions over other substrates. The cleavage activity was monitored in fixed time assays, showing that, as with vaccinia resolvase, the fowlpox enzyme could cleave a wide array of branched DNA substrates. Single turnover kinetic analysis revealed the Holliday junction substrate was cleaved 90-fold faster than a splayed duplex substrate containing a single to double strand transition. Multiple turnover kinetic analysis, however, showed that the cleavage step was not limiting for the full reaction cycle. Cleavage by resolvase was also tightly coupled at symmetrical positions across the junction, and coupling required the complete Holliday junction structure. Last, we found that cleavage of an extruded cruciform yielded a product, which after treatment with ligase, had the properties expected for covalently closed DNA hairpin ends, as is seen for poxvirus genome monomers. These findings provide a tractable poxvirus resolvase usable for the development of small molecule inhibitors.